2015
DOI: 10.1080/02757540.2015.1039527
|View full text |Cite
|
Sign up to set email alerts
|

Role of arbuscular mycorrhizal fungi on the performance of floodplainPhragmites japonicaunder nutrient stress condition

Abstract: A pot experiment was conducted to evaluate the potential effects of arbuscular mycorrhizal fungi (AMF) on growth, nutrient uptake, and inoculation effectiveness on Phragmites japonica. Spores of AMF strains (Gigaspora margarita Becker & Hall) were collected from the commercial product 'Serakinkon'. Four treatments, namely, natural soil (NS), natural soil inoculated by AM fungi, sterilised soil (SS) inoculated by AM fungi, and SS without AM fungi inoculation were selected to determine the effects of applied and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In our study sites, the groundwater seepage was 3 m below the soil surface (Asaeda et al , ), and the observed depths of rhizospheric zones of vegetation indicated that plants were capable of taking up nitrogen only from the unsaturated zone of the soil. While the mycorrhizal association of some plants may increase the rhizospheric zone to some extent (Sarkar et al , ), we assume that the enrichment of nutrients in surface soil throughout this process is negligible (Evans, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study sites, the groundwater seepage was 3 m below the soil surface (Asaeda et al , ), and the observed depths of rhizospheric zones of vegetation indicated that plants were capable of taking up nitrogen only from the unsaturated zone of the soil. While the mycorrhizal association of some plants may increase the rhizospheric zone to some extent (Sarkar et al , ), we assume that the enrichment of nutrients in surface soil throughout this process is negligible (Evans, ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study sites, the groundwater seepage was 3 m below the soil surface (Asaeda et al, 2010), and the observed depths of rhizospheric zones of vegetation indicated that plants were capable of taking up nitrogen only from the unsaturated zone of the soil. While the mycorrhizal association of some plants may increase the rhizospheric zone to some extent (Sarkar et al, 2015), we assume that the enrichment of nutrients in surface soil throughout this process is negligible (Evans, 2001). Denitrification is one of the most effective processes of nitrogen loss from sediment (Saunders and Kalff, 2001) and from terrestrial soil under certain conditions of soil moisture, oxygen, inorganic nitrogen and respirable carbon (Groffman, 2012).…”
Section: Nitrogen Enrichment Processes In Soilmentioning
confidence: 99%
“…AMF-root symbiosis may help alleviate some of the problems that the plants encounter when grown in acidic soils (Li et al 1991) including Al and/or Mn toxicity. Mycorrhizal fungi functions in promoting plant growth across floodplain chronosequences were described by Sarkar et al (2015b). But their functions in promoting plant growth are unknown across hilly region having low nutrients content.…”
Section: Introductionmentioning
confidence: 99%